Feminist Interpretations Of Misogynistic Qur'an And Hadith: Strategies For Promoting Feminism In Indonesia And Malaysia - Muqtada, Muhammad Rikza; Istianah; bin Mustapha , Ahmad Sharifuddin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2024)
This paper discusses the discourse of interpretation of the Qur'an and misogynistic hadith by feminist activists in Indonesia and Malaysia as a strategy in promoting feminism in their respective countries. For this reason, the discussion focuses on interpretation methods, production of feminist interpretations, and dissemination of feminist interpretation. The study is qualitative research in which data is taken through interviews, observations, and documentation. The results of the study show that 1) The interpretation of the Qur'anic texts and hadith is done by seeing them as open and constantly developing texts. It means that texts could respond and interact with modern knowledge such as gender, law, and human rights. 2) The feminist approach to the Qur'an and hadith involves misogynistic challenges including marginalization, stereotypes, subordination, and violence against women. It also looks at the multiple roles of women and their subordination 3) Feminist interpretation is socialized by feminist activists from Islamic boarding schools and university backgrounds. They took part in discussions and wrote about feminism in magazines and social media. They also participate in women's organizations that advocate women protection and campaign for women's rights including the hazards of polygamy. This study shows that power relations within organizations have a significant impact on the interpretation of religious texts. This interpretation was then used to motivate women activists to promote feminism. [Tulisan ini mendiskusikan wacana penafsiran al-Qur’an dan hadis misoginis oleh para aktivis feminisme di Indonesia dan Malaysia sebagai strategi dalam mempromosikan feminisme di negara masing-masing. Untuk itu, pembahasan akan terfokus pada metode penafsiran, produksi tafsir feminis, dan diseminasi penafsiran feminisme. Kajian bersifat lapangan dengan mengambil data melalui wawancara, observasi, dan dokumentasi. Teknik analisis data melalui reduksi, penyajian, dan penarikan kesimpulan. Pendekatan yang digunakan adalah feminisme. Hasil penelitian menunjukkan bahwa 1) Penafsiran teks-teks al-Qur'an dan hadis dilakukan dengan melihatnya sebagai sesuatu yang terbuka dan terus berkembang. Artinya teks harus terus berinteraksi dengan pengetahuan modern seperti gender, hukum, dan hak asasi manusia. Hal ini membuat teks lebih mudah dipahami. 2) Pendekatan feminis terhadap Al-Qur'an dan hadits melibatkan tantangan misoginis termasuk marjinalisasi, stereotip, dan kekerasan terhadap perempuan. Pendekatan ini juga melihat peran ganda perempuan dan subordinasi mereka. 3) Tafsir feminis disosialisasikan oleh para aktivis feminis yang berlatar belakang pesantren dan universitas. Mereka ikut serta dalam diskusi dan menulis tentang feminisme di majalah dan media sosial. Mereka juga ikut serta dalam organisasi perempuan yang mengkampanyekan hak-hak perempuan termasuk bahaya poligami dan mengadvokasi lembaga Pemerintah untuk melindungi perempuan. Penelitian ini menunjukkan bahwa relasi kuasa dalam organisasi memiliki dampak yang signifikan terhadap penafsiran teks-teks agama. Interpretasi ini kemudian digunakan untuk memotivasi para aktivis perempuan untuk mempromosikan feminisme.]